Rasch Model Application: Instrument Development of Readiness to Conduct Inclusive Learning - Ratna Sari; M Nurul Ikhsan Saleh (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2022)
This study aims to analyze development of an instrument that measures the level of readiness of Islamic Education (PAI) prospective teachers in conducting inclusive learning. The process was conducted by investigating three important indicators, namely: (1) motivation and value, (2) content-related, and (3) operational and pragmatist. The method employed was a non-experimental quantitative design which was considered a pilot test. Data were collected from 144 samples of PAI students who are prospective teachers from two private universities in Yogyakarta, and the tool used was a questionnaire which was analyzed using Rasch Model measurement software called WINSTEPS. Furthermore, it was used to determine the validity and reliability of items, respondents, and instrument. The results showed that development of readiness instrument in conducting inclusive learning using Rasch model consisted of 34 items with a coefficient of instrument, item, and respondent reliability of 92, 90, and 92, respectively. Therefore, it was discovered that instrument has good psychometric properties and can be used effectively.